One Year Duration of Immune Response Following a 3rd Booster Dose of mRNA Vaccine Against COVID‐19 in 292 Patients With Hematological Malignancies in University Hospital Ostrava, Czech Republic - Ondrej Šušol; Barbora Šušolová; Ondřej Klempíř; Milan Navrátil; Jaromír Gumulec; Zdeněk Kořístek; Juraj Ďuraš; Michal Kaščák; Jana Mihályová; Lukáš Stejskal; Tomáš Jelínek; Petra Richterová; et al. (Cancer Medicine)
ABSTRACT Aims To evaluate antibody response to mRNA vaccine, identify subgroups with poor response and to determine long‐term antibody durability in hematological patients. Materials and Methods We have vaccinated 292 patients with all hematological malignancies with a third dose of mRNA COMIRNATY vaccine with a 12‐month follow‐up period in our center in Ostrava, Czech Republic. Results Antibody response for the whole cohort exceeded 74% through the whole 12‐month follow‐up. Lowest seroconversion was observed in CLL cohort (20/41, 48.8%), patients who received anti‐CD20 therapy < 6 months before vaccination (8/30, 26.7%) and BTK inhibitors (3/6, 50.0%). On the contrary, patients with chronic myeloproliferative neoplasms and acute leukemia performed comparably with healthy population (33/33; 100% and 12/13; 92.3%, respectively). We have seen better results if the time interval between anti‐CD20 therapy and additional vaccine dose was longer than 6 months (5/8 patients achieved seroconversion on 4th booster dose after previous failure). Also, 36 patients received a 4th dose of vaccine as a booster with measurable increase in protective antibodies in 50% (18/36). Conclusions Additional doses show promise for a well‐timed revaccination even in poor responders. To our knowledge, no study comparable to our work in terms of follow‐up length, vaccine consistency or variety of hematological malignancies and/or treatment has been reported yet. Our findings shed more light on long‐term antibody response to mRNA vaccines against SARS‐CoV‐2 in patients with hematological cancer and bring important data for the evaluation of possible vaccine failure and scheduling of subsequent doses.